2009
DOI: 10.1007/s10072-009-0198-4
|View full text |Cite
|
Sign up to set email alerts
|

Reported quality of randomized controlled trials in neglect rehabilitation

Abstract: The aim of this study is to assess the reported quality of randomized controlled trials (RCTs) on the effectiveness of neglect rehabilitation using a standardized scale. A search of seven electronic databases was carried out. Selected articles were scored using the PEDro scale and classified as high or low quality study both with the original cut off of 6 and a modified cut off of 5. A linear regression analysis between year of publication and quality rate was used to test whether the quality of the studies im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…Discrepancies were resolved by discussion including the third reviewer if required. Trials which scored 6 or higher in the PEDro scale were considered to be of good quality, while those which scored less than 6 were considered to be of poor quality 5 | P a g e (15). Data were extracted from each study by one reviewer (HA).…”
Section: Quality Appraisal and Data Extractionmentioning
confidence: 99%
“…Discrepancies were resolved by discussion including the third reviewer if required. Trials which scored 6 or higher in the PEDro scale were considered to be of good quality, while those which scored less than 6 were considered to be of poor quality 5 | P a g e (15). Data were extracted from each study by one reviewer (HA).…”
Section: Quality Appraisal and Data Extractionmentioning
confidence: 99%
“…In a Cochrane review excluding all studies that were not considered properly randomized controlled trials, Bowen and Lincoln (2007) conclude that there is insufficient evidence to support the effectiveness of specific cognitive rehabilitation approaches for reducing disabilities due to neglect (see also Rohling et al, 2009; Paci et al, 2010). However, in two reviews of cognitive rehabilitation, Cicerone et al (2000, 2005) recommend visual scanning training as a practice standard for the treatment of neglect.…”
Section: Introductionmentioning
confidence: 99%
“…Fifteen randomized trials were identified, of which six presented a crossover design. All studies were classified as "good quality" by the PEDro scale (Foundation, 2017;Maher, 2000;Maher et al, 2003;Moseley et al, 2002;Paci et al, 2010;Zou et al, 2017). Due to heterogeneity in the use of antidepressants, the findings will be presented according to clusters of these clinical indications (Ehrnrooth et al, 2001;Etzel et al, 1991;Feinmann et al, 1984;Forssell et al, 2004;Maina et al, 2002;Moghadamnia et al, 2009;Mohamed et al, 1997;Movassaghian et al, 2011Movassaghian et al, , 2013Raigrodski, Christensen, et al 2001;Rizzatti-Barbosa et al, 2003;Sardella et al, 2008;Sharav et al, 1987;Tammiala-Salonen & Forssell, 1999).…”
Section: Discussionmentioning
confidence: 99%